BSA imprinted polyethylene glycol grafted calcium alginate hydrogel microspheres. Issue 36 (30th May 2016) - Liu, Jiangquan; Ying, Xiaoguang; Wang, Hongxun; Li, Xiao; Zhang, Weiying
ABSTRACT: Polyethylene glycol grafted calcium alginate hydrogel microspheres are synthesized by ring‐opening and addition reaction of epoxy chloropropane. FTIR, 13 C NMR, optical microscope, SEM, TG, and DSC are used for characterization. Swelling behaviors are studied and it is found that polyethylene glycol grafted calcium alginate microspheres are improved in anti‐swelling properties. Protein‐imprinted polyethylene glycol grafted calcium alginate hydrogel microspheres exhibit enhanced specific rebinding quantity (11.16 mg/g) and selective recognition properties (4.71 against BHb), towards target molecule in the presence of competing protein, compared with that of the unmodified samples (4.96 mg/g and 1.75, respectively). © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 43617. Abstract :